DETERMINATION OF EMPLOYEE JOB SATISFACTION PT BANK SYARIAH MANDIRI - ira widya; arbanur rasyid; muhammad wandisyah; m fauzan (Journal Of Sharia Banking, 2021)
Fluctuations that occur in the number of employees at PT Bank Syariah Mandiri Gunung Tua Sub-Branch Office, which indicates employee dissatisfaction. The fluctuation that occurred was caused by several employees who applied for resignation for several reasons as well as employee dismissal due to not achieving the target. The formulation of the problem in this study is whether the influence of work environment, competence, and career development has an influence on employee job satisfaction. The aim is to determine whether there is an influence of these three variables on employee job satisfaction at PT Bank Syariah Mandiri Gunung Tua Sub-Branch Office. This research is a quantitative study with sampling using saturated samples with a sample size of 17. The data collection technique uses literature study, interviews, documentation and questionnaires. Data analysis techniques include instrument test (validity test, reliability test), classic assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (determination coefficient test (R2), t test, F test). To simplify the data analysis process, this research was assisted by the SPSS version 23 program. The results of the t test showed that there was no influence of the work environment on employee job satisfaction, there was no influence between competence on employee job satisfaction, and there was an influence between career development on employee job satisfaction. Simultaneously there is an influence between work environment, competence, and career development on employee job satisfaction.